The "unknown territory" of goal-setting: Negotiating a novel interactional activity within primary care doctor-patient consultations for patients with multiple chronic conditions. (July 2020) - Murdoch, Jamie; Salter, Charlotte; Ford, John; Lenaghan, Elizabeth; Shiner, Alice; Steel, Nicholas
Abstract: Goal-setting is widely recommended for supporting patients with multiple long-term conditions. It involves a proactive approach to a clinical consultation, requiring doctors and patients to work together to identify patient's priorities, values and desired outcomes as a basis for setting goals for the patient to work towards. Importantly it comprises a set of activities that, for many doctors and patients, represents a distinct departure from a conventional consultation, including goal elicitation, goal-setting and action planning. This indicates that goal-setting is an uncertain interactional space subject to inequalities in understanding and expectations about what type of conversation is taking place, the roles of patient and doctor, and how patient priorities may be configured as goals. Analysing such spaces therefore has the potential for revealing how the principles of goal-setting are realised in practice. In this paper, we draw on Goffman's concept of 'frames' to present an examination of how doctors' and patients' sense making of goal-setting was consequential for the interactions that followed. Informed by Interactional Sociolinguistics, we used conversation analysis methods to analyse 22 video-recorded goal-setting consultations with patients with multiple long-term conditions. Data were collected between 2016 and 2018 in three UK general practices as part of a feasibility study. We analysed verbal and non-verbal actions for evidence of GP and patient framings of consultation activities and how this was consequential for setting goals. We identified three interactional patterns: GPs checking and reframing patients' understanding of the goal-setting consultation, GPs actively aligning with patients' framing of their goal, and patients passively and actively resisting GP framing of the patient goals. These reframing practices provided "telling cases" of goal-setting interactions, where doctors and patients need to negotiate each other's perspectives but also conflicting discourses of patient-centredness, population-based evidence for treating different chronic illnesses and conventional doctor-patient relations. Highlights: First study of GP goal-setting interactions for patients with multiple conditions. Goal-setting involves novel activities in an uncertain interactional space. GPs and patients may need to negotiate different framings of patient's priorities. GPs may actively align with patient's goal, patients may resist GP framing of goal. Negotiation of frames reveal conflicting discourses invoked at interactional level.